Concurrent oral human papilloma virus infection in patients with recurrent respiratory papillomatosis: A preliminary study. (24th July 2014) - Born, Hayley; Ruiz, Ryan; Verma, Avanti; Taliercio, Salvatore; Achlatis, Stratos; Pitman, Michael; Gandonu, Sonate; Bing, Renjie; Amin, Milan R.; Branski, Ryan C.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To determine oral human papilloma virus (HPV) colonization in patients with adult‐onset recurrent respiratory papillomatosis (AO‐RRP) and their long‐term partners. Study Design Prospective, cohort study Methods Patients with pathology‐confirmed AO‐RRP and a small cohort of their long‐term partners were subjected to a standardized oral rinse and swab protocol to obtain oral epithelial cells. DNA from these samples was extracted and subjected to both qualitative analyses via multiplex polymerase chain reaction as well as to a commercially available linear array assay for the determination of specific HPV subtypes. Results Samples were collected from 27 patients with AO‐RRP and six long‐term sexual partners. Qualitative analysis of agarose gel products using a multiple genotype primer cocktail suggested the presence of HPV DNA in oral rinse or swabs in 26 patients (96%) and four partner samples (67%). A subset of these positive patient samples was then subjected to genotyping; a spectrum of HPV subtypes was observed. Interestingly, HPV81 was identified in many samples. Conclusion Recent data suggest that less than 7% of the general population is HPV positive in the oral cavity. Our data suggest that the oral colonization rate is much higher in patients with AO‐RRP. Additionally, long‐term sexual partners of patients with RRP had a much higher rate of HPV positivity. These preliminary data may have implications for viral transmission and provide a framework for enhanced patient education as well as further investigation. Level of Evidence 4. Laryngoscope, 124:2785–2790, 2014